Single and Two-Phase Heat Transfer Enhancement Using Longitudinal Vortex Generator in Narrow Rectangular Channel - Huang, Yan-Ping; Huang, Jun; Ma, Jian; Wang, Yan-Lin; Wang, Jun-Feng; Wang, Qiu-Wang (IntechOpen, 2012)
None